2016
DOI: 10.1038/ncomms12173
|View full text |Cite
|
Sign up to set email alerts
|

Plastid-nucleus communication involves calcium-modulated MAPK signalling

Abstract: Chloroplast retrograde signals play important roles in coordinating the plastid and nuclear gene expression and are critical for proper chloroplast biogenesis and for maintaining optimal chloroplast functions in response to environmental changes in plants. Until now, the signals and the mechanisms for retrograde signalling remain poorly understood. Here we identify factors that allow the nucleus to perceive stress conditions in the chloroplast and to respond accordingly by inducing or repressing specific nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 71 publications
1
65
0
Order By: Relevance
“…In fact, evidence for this scenario was provided recently by the finding that ABI4, a central TF involved in different chloroplast retrograde signaling pathways, was phosphorylated by the MAP kinase MPK6 in a Ca 2+ -dependent manner (Guo et al, 2016). Strikingly, MPK6 also was recently found to be regulated by SnRK1 under hypoxia conditions (Cho et al, 2016).…”
Section: Anterograde Signals To Organelles Via Phosphorylation Of Tramentioning
confidence: 88%
“…In fact, evidence for this scenario was provided recently by the finding that ABI4, a central TF involved in different chloroplast retrograde signaling pathways, was phosphorylated by the MAP kinase MPK6 in a Ca 2+ -dependent manner (Guo et al, 2016). Strikingly, MPK6 also was recently found to be regulated by SnRK1 under hypoxia conditions (Cho et al, 2016).…”
Section: Anterograde Signals To Organelles Via Phosphorylation Of Tramentioning
confidence: 88%
“…Further work is needed to indentify the specific signals that drive ANN5-dependent reprogramming of plastid function. Recent studies revealed that retrograde regulation of the nuclear gene expression involved calcium signaling [37]. Calcium ions were released from the plastids to the cytosol in response to specific stimuli [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emerging evidence indicates that chloroplasts contribute to cellular Ca 2+ -homeostasis and signaling and identified the chloroplast Ca 2+ sensor protein (CAS) as a central component in these processes (Nomura et al, 2007(Nomura et al, , 2012Weinl et al, 2008;Petroutsos et al, 2011;Hochmal et al, 2015). In Arabidopsis, CAS crucially functions in the generation of cytosolic and stromal Ca 2+ transients as well as in the modulation of MAPK signaling (Guo et al, 2016). Moreover, it is involved in photo-acclimation in Chlamydomonas reinhardtii by contributing to the control of expression of LHCSR3 and to the expression of proteins related to the carbon-concentrating mechanism (Petroutsos et al, 2011;Wang et al, 2016b).…”
Section: Ca 2+ Signaling In Mitochondria and Chloroplastsmentioning
confidence: 99%